SECONDARY EFL STUDENTS’ MOTIVATION AND SELF-CONFIDENCE WITH AI-MEDIATED WRITING FEEDBACK - Annisa; Siti Zulaiha; Herri Mulyono; Jihana Fakhira (University of Kuningan, 2026)
This qualitative study investigated secondary EFL students’ perceived changes in motivation and self-confidence when Ginger Writer feedback was integrated into classroom writing. The study was conducted in a public junior high school in Jakarta, Indonesia. The classroom implementation involved 25 eighth-grade students, and 10 students consented to participate in semi-structured interviews conducted via WhatsApp call (20–30 minutes). Ginger Writer was integrated over five 80-minute sessions through descriptive, recount, and collaborative writing activities. Interview data were analysed thematically to examine how learners interpreted and used AI-mediated feedback and how these experiences related to motivation and self-confidence. Findings indicate that students perceived Ginger Writer as supportive when feedback was actionable during drafting and revision and when visible progress encouraged continued revising. However, motivational change was conditional: reduced engagement was reported when error volume felt overwhelming or when suggestions were difficult to interpret. Students generally reported increased self-confidence, particularly in willingness to write and submit assignments, yet confidence development appeared uneven and sometimes remained partially tool-dependent. Teacher guidance and peer discussion were perceived as important mediators supporting feedback interpretation and authorship, while connectivity issues and perceived overreliance constrained uptake. The study highlights the value of positioning AI feedback as a scaffold within a mediated feedback system and of teaching feedback literacy to support transfer beyond tool-supported performance.